The Relationship Between Phbs Factors And The Incidence Of Diarrhea In Toddlers - Ziyana, Ziyana; Maritalia, Dewi; Malia, Anna (Universitas Prima Indonesia, 2025)
Diarrhea remains a major health problem among infants in Indonesia, and various factors related to clean and healthy living behaviors (PHBS) are believed to play an important role in reducing its incidence. In 2021, diarrhea accounted for approximately 9% of all infant deaths worldwide. This equates to more than 1,200 child deaths per day, or approximately 444,000 children per year. The objective of this study was to determine the relationship between PHBS factors and the incidence of diarrhea among infants in the Peusangan Selatan Health Center District, Bireuen Regency, in 2025. The research method used was correlation analysis with a cross-sectional design, i.e., a study conducted through observation or data collection at a specific point in time. The study population consisted of mothers with infants in May 2025, totaling 864 infants, with a sample size of 91 respondents selected using non-probability sampling. The research tool was a structured questionnaire developed based on theory and references related to PHBS. The results of the multivariate analysis showed that the variable of healthy toilet use had a significant effect on the incidence of diarrhea in toddlers (p = 0.000; Exp(B) = 37.610), while the use of clean water (p = 0.997) and hand washing (p = 0.625) did not show a significant effect.